Video narratives to assess student teachers' competence as new teachers. Issue 1 (2nd January 2016) - Admiraal, Wilfried; Berry, Amanda
Abstract : In teacher education programmes, written portfolios or text-based self-evaluations are generally used to document the development of student teachers' competence. However, such approaches do no justice to the complex nature of teaching as they tend to lead to evidence in which teacher competencies are disconnected and removed from the actual teaching practice. In one postgraduate teacher education programme, video narratives were evaluated as a valid way to assess student teachers' teaching competencies, promoting connections amongst different competencies, situating these in practice and showing their development over time. Data were gathered from self-reports of both teacher educators and student teachers as well as student teachers' completed video narratives. Most student teachers succeeded in meeting the set criteria for the video narrative assignment with connected video clips and text frames. However, student teachers also came up with only a few video episodes and loosely connected clips, reflections and other sources. Although most of the students during the programme did explicitly reflect upon their personal development towards becoming a teacher, almost none of them explicitly connected these ideas to their long-term development. We conclude that video narratives show potential to be used as a valid assessment of student teachers' teaching competence. Yet, structured guidance as well as ill-structured assignments are needed in framing assessment of student teachers in teacher preparation: the former to clarify the aims, format and criteria and the latter to enable student teachers to reflect on their teaching in a personally, meaningful way.